WORD FORMATION USED IN J+ NEWSPAPER - Cicih Nuraeni (LPPM Universitas Bina Sarana Informatika, 2018)
Aronoff, Mark, and Kirsten Fudeman. 2011. Fundamental Of Linguistics: What Is Morphology?. 2nd ed. United Kingdom: Willey-Blackwell.Carstairs, Andrew and McCarthy. 2002. An Introduction To English Morphology: Words And Their Structure. United Kingdom: Edinburgh University Press, Ltd.Haspelmath, Martin and Sims. 2010. Understanding Language Series: Understanding Morphology. 2nd ed. United Kingdom: Hodder Education.Hill, Archibald. A. 1969. Voice Of America Forum Series: Linguistics. Washington, D.C.: Voice Of America.J+ Newspaper. 2016. Your Weekly Lifestyle Supplement. Jakarta: J+ by The Jakarta Post, VOL 34. NO. 106 – 2016. (September 3, 2016)Lieber, Rochelle. 2009. Introducing Morphology. New York: Cambridge University Press.Meyer, Charles. F. 2009. Introducing English Linguistics. New York: Cambridge University Press.O’Grady, William, Michael Dobrovolsky and Francis Katamba. 1997. Contemporary Linguistics: An Introduction. Adapted Version. Adisson Wesley Longman, Ltd.Oxford Advanced Learner’s Dictionary. 7th ed. Oxford University PressPlag, Ingo. 2002. Word-Formation In English. Draft Version. Cambridge University Press. Available from http://www2.uni-siegen.de/ engspra/plag-in-press.pdf (May 8, 2015)Yule, George. 2010. The Study of Language. 4th Ed. New York: Cambridge University Press.Zapata, Argenis. A. 2007. Unit 1: Types Of Words And Word-Formation Processes In English. Universidad de Los Andes. Available from http://webdelprofesor.ula.ve/humanidades/azapata/materias/english_4/unit_1_types_of_words_and_word_formation_processes.pdf (May 8, 2015)